Design And Implementation Of Low Passband Ripple Digital Down Converter Filter For Software Defined Radio Transceiver - Naghmash, Majid Salal (2011)
The main aim of this research is the design and implementation of the Digital Down Converter (DDC) filter with low passband ripple and high attenuation in the adjacent rejection and blocker requirements in the filter response for Software Defined Radio (SDR) transceiver to decrease the power consumption and avoid the interference in the channel. The proposed DDC filters incorporate of Remez algorithm and Mini-max algorithm to reduce the error rate in the filter response. The DDC filter is acombination of 5-stages Cascaded Integrated Comb (CIC) filter and two linear phase Equiripple FIR filter (CFIR and PFIR). The passband ripple, adjacent rejection and blocker band is developed by controlling the transition width, filter order and weight function of the FIR filter using MATLAB and Xilinx System Generator environment.